Longarm and the Banker's Daughter - Evans, Tabor (Evans, Tabor. Longarm., 2012)
Deputy U.S. Marshal Custis Long must bring a curvaceous con-artist, who, using her feminine wiles, has double-crossed her banker father, the outlaws who've robbed her father's bank, and countless others, to justice.